Kajian Psikoanalisis Sigmund Freud terhadap Luka Batin Tokoh Utama dalam Novel Broken Strings Karya Aurélie Moeremans : Sigmund Freud's Psychoanalytic Study of the Main Character's Inner Wounds in Aurélie Moeremans' Novel Broken Strings - Rosyida Tamami (Information Technology and Science(ITScience), 2026)
This study analyzes the main character's inner wounds in the novel Broken Strings using Sigmund Freud's psychoanalytic approach, focusing on the personality structures of the id, ego, and superego. The method used is a descriptive, qualitative approach with a literary psychology perspective. The research data consists of quotations from the novel that reveal the main character's inner wounds. Data collection was carried out through reading and note-taking. In contrast, the data analysis used content analysis, with the stages of identification, classification, interpretation, and conclusion drawing, based on Freud's psychoanalytic theory. The results show that an imbalance among the id, ego, and superego forms the main character's inner wounds. The id aspect appears in the form of spontaneous emotional responses such as fear, panic, anxiety, and the desire to avoid situations that trigger traumatic experiences. The ego aspect shows a weakened function due to repeated psychological pressure, leading the character to compromise, rationalize, and surrender to situations that are detrimental to him. The superego becomes the dominant personality structure through the emergence of excessive guilt, heightened moral demands, and a tendency to blame himself. The dominance of the superego deepens the character's inner wounds by fostering ongoing psychological pressure. This research shows that emotional wounds in literary works are influenced not only by characters' traumatic experiences but also by the dynamics of the relationship among the id, ego, and superego. The research findings enrich the study of literary psychology by demonstrating that Freud's personality structure can be used to explain the process of formation and persistence of emotional wounds in literary characters.